2019
DOI: 10.4103/jpbs.jpbs_22_19
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental anxiety level in 6- to 12-year-old South Indian children

Abstract: Background: Dental anxiety is one of the prime reasons for discouraging children to receive dental treatment. Measurement of the dental anxiety is very useful to know the prevalence level among 6- to 12-year-old children. Thus, the aim of the study was to determine the dental anxiety among 6- to 12-year-old children using Modified Dental Anxiety Scale (MDAS) score. Materials and Methods: A total of 400 south Indian children in the age group of 6-12 years who had visited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
1
3
1
Order By: Relevance
“…The mean score of DFA in the children of 6 to 11 years (11.89 ± 4.84) was higher than those reported by the vast majority of researchers, 24 25 but lower than the values reported by Kumar et al (2019). 19 The mean score of DFA in the children of 12 to 17 years (10.27± 3.16) was lower than the values found in the literature. 26 Generally, these findings are consistent with the reports that DFA seems to decrease with increasing age.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The mean score of DFA in the children of 6 to 11 years (11.89 ± 4.84) was higher than those reported by the vast majority of researchers, 24 25 but lower than the values reported by Kumar et al (2019). 19 The mean score of DFA in the children of 12 to 17 years (10.27± 3.16) was lower than the values found in the literature. 26 Generally, these findings are consistent with the reports that DFA seems to decrease with increasing age.…”
Section: Discussioncontrasting
confidence: 61%
“…Children with a total MDAS score of 19 or more have been considered to be very high anxious, 15 to 18 anxious, 11 to 14 moderate, 5 to 6 low, and 0 to 5 no anxiety. 19…”
Section: Survey Instrumentmentioning
confidence: 99%
“…it can be seen that the gender of girls is more likely to have moderate anxiety than boys. The results of the study are in line with research conducted by Vinod et al [12], that respondents with low and high levels of anxiety are more likely to be found in girls than boys. The results of this study are also in line with Al-Saddi, that anxiety in dental care is higher in girls respondents than boys [24].…”
Section: Discussionsupporting
confidence: 91%
“…Research conducted by Vinod et al [12], it was found that 63.24% of girls felt anxious about dental treatment compared to 55.42% of boys. Research conducted by Hamudeng [13], that based on gender, there were differences in anxiety levels between boys and girls, girls were significantly more anxious than boys.…”
mentioning
confidence: 95%
“…1 In a study conducted by Vinod Kumar et al, among South Indian children aged 6-12 years, the prevalence of dental anxiety in children was seen to be high (84.4%). 2 Thereby, to reduce stress during dental treatment, behaviour management strategies can be incorporated which are broadly divided into two categories. The conventional techniques include non-pharmacological behavioural techniques (distraction, tell-show-do, modelling, desensitisation etc.)…”
Section: Introductionmentioning
confidence: 99%